The HSP90 Inhibitor, 17-AAG, Influences the Activation and Proliferation of T Lymphocytes via AKT/GSK3β Signaling in MRL/lpr Mice - Hong, Liang-Jian; Chen, Ai-Jun; Li, Feng-Zeng; Chen, Ke-Jun; Fang, Sheng (Drug design, development and therapy, 2020)
To explore the molecular mechanism of 17-AAG in the treatment of systemic lupus erythematosus (SLE), and the effects of the heat shock protein 90 (HSP90) inhibitor 17-AAG on the activation and proliferation of lymphocytes and the AKT/GSK3β signaling pathway in MRL/lpr mice were detected. MRL/lpr mice were randomly divided into the control group and the experimental group. The experimental group was injected intraperitoneally with 17-AAG, and T lymphocytes were separated by magnetic beads. Lymphocyte proliferation was detected by MTT and flow cytometry (FCM), and the expression of the HSP90 protein and PI3K/AKT signaling pathway-related proteins was detected by Western blotting. Renal histopathology and immune complex deposition were also observed in both groups. Immune complex deposition and inflammation decreased in kidneys from MRL/lpr mice in the experimental group. HSP90 protein expression, T lymphocyte proliferation and phosphorylated AKT and GSK3β levels also decreased in the experimental group. 17-AAG can inhibit the activation and proliferation of T lymphocytes and downregulate the AKT/GSK3β signaling pathway, which may be relevant for the treatment of SLE.